Process and outputs from a community codesign workshop on reducing impact of heat exposure on pregnant and postpartum women and newborns in Kilifi, Kenya - Lusambili, Adelaide; Khaemba, Peter; Agoi, Felix; Oguna, Martha; Nakstad, Britt; Scorgie, Fiona; Filippi, Veronique; Hess, Jeremy; Roos, Nathalie; Chersich, Mathew; Kovats, Sari; Luchters, Stanley (Frontiers in Public Health, 2023)
Background: Ambient heat exposure is increasing due to climate change and is known to affect the health of pregnant and postpartum women, and their newborns. Evidence for the effectiveness of interventions to prevent heat health outcomes in east Africa is limited. Codesigning and integrating local-indigenous and conventional knowledge is essential to develop effective adaptation to climate change.Methods: Following qualitative research on heat impacts in a community in Kilifi, Kenya, we conducted a two-day codesign workshop to inform a set of interventions to reduce the impact of heat exposure on maternal and neonatal health. Participants were drawn from a diverse group of purposively selected influencers, implementers, policy makers, service providers and community members. The key domains of focus for the discussion were: behavioural practices, health facilities and health system factors, home environment, water scarcity, and education and awareness. Following the discussions and group reflections, data was transcribed, coded and emerging intervention priorities ranked based on the likelihood of success, cost effectiveness, implementation feasibility, and sustainability.